Exercise training exerts beneficial effects on Alzheimer’s disease through multiple signaling pathways - Kang, Jihe; Liu, Mei; Yang, Qiang; Dang, Xiangji; Li, Qun; Wang, Ting; Qiu, Bin; Zhang, Yibao; Guo, Xudong; Li, Xiaoling; Liu, Yan (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disease characterized by progressive memory loss and cognitive dysfunction that affects millions of people worldwide, placing a massive burden on families and economies. Exercise training can effectively reduce the prevalence of AD and alleviate its symptoms through the modulation of multiple signaling pathways involved in the pathophysiological process of AD, including the PI3K/Akt, Wnt/β-catenin, AMPK-related, MAPK, NF-κB, PINK1-PARKIN, JAK/STAT, and TREM2 signaling pathways. Different signaling pathways also crosstalk with each other through different targets to inhibit the formation of Amyloid β (Aβ) plaques, reduce the level of hyperphosphorylated tau protein, reduce apoptosis, relieve neuroinflammation, reduce autophagy dysfunction, and ultimately improve cognitive impairment in AD patients. This review summarizes the pathophysiological processes of AD affected by exercise training through different signaling pathways. We further provide a reference for the future development of new effective AD prevention and treatment targets to develop promising personalized, combined intervention strategies.